2017
DOI: 10.3389/fpubh.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Antenatal Care, Skilled Birth Attendance, and Postnatal Care Utilization among the Remote and Poorest Rural Communities of Zambia: A Multilevel Analysis

Abstract: ObjectiveOptimal utilization of maternal health-care services is associated with reduction of mortality and morbidity for both mothers and their neonates. However, deficiencies and disparity in the use of key maternal health services within most developing countries still persist. We examined patterns and predictors associated with the utilization of specific indicators for maternal health services among mothers living in the poorest and remote district populations of Zambia.MethodsA cross-sectional baseline h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
66
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 39 publications
14
66
2
2
Order By: Relevance
“…In agreement with this research, Mohan et al [23] reported no signi cant association between community-level distance to a health facility and PNC services utilization. Also similar to this study, some researchers reported that the association between use of PNC services and area of residence was not signi cant [25,46]. In addition, a study by Darega et al [47] found no signi cant association between employment status and the use of PNC services.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In agreement with this research, Mohan et al [23] reported no signi cant association between community-level distance to a health facility and PNC services utilization. Also similar to this study, some researchers reported that the association between use of PNC services and area of residence was not signi cant [25,46]. In addition, a study by Darega et al [47] found no signi cant association between employment status and the use of PNC services.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, Worku et al [22] found no signi cant area-level effects on the use of PNC services. Some multilevel studies in Tanzania [23], Nigeria [24], Zambia [25], Kenya [26] and India [27,28] reported that a community-level effect strongly predicted PNC services use, after controlling for individual-level predictors. In addition, these previous studies estimated different community-level effects of communities on the utilization of PNC services; for example Mohan et al [23] and Solanke et al [29] reported that 12% and 37.2% unexplained community variance respectively accounted for the variability in PNC services use.…”
Section: Ghana Had 10 Administrative Regions During the 2014 Ghana Dementioning
confidence: 99%
“…Full service was measured as when women's received the seven selected essential antenatal care services (blood pressure measurement, blood sample collection, urine sample collection, tetanus toxoid(TT2+) vaccination, iron foliate(90+) supplementation and health education on danger signs and nutrition). Full services was considered as not received when one of the seven selected elements of antenatal care services was not provided during ANC visit [21,26]. Means of transportation to health facilities was classified as on foot, by bicycles, or by car [18,19].…”
Section: Different Groups Of Explanatory Variables Have Been Considermentioning
confidence: 99%
“…Sociodemographic and economic factors including higher maternal education [9][10][11][12][13][14][15][16][17][18], higher wealth quintile [9,11,15], and employed by occupation [11] were found to have a positive association with health facility childbirth. Antenatal care attendance [9][10][11][12][13][14][15][16][17][18][19], birth order [10,14,15], previous childbirth in health facility [17], closer distance to health facility and access to transport [15], known pregnancy complication [9], planning to give birth in health facility [14], and quality of care [15] were also the factors that influenced women to utilise skilled birth attendance service. Furthermore, a community-based cross-sectional study conducted in North West Ethiopia revealed that fear and occurrence of complications, getting better service, safe and clean delivery, being informed to deliver at health facility during antenatal care, antenatal care attendance, and positive attitude of health workers were the main reasons for choosing skilled delivery service [13].…”
Section: Introductionmentioning
confidence: 99%